ASSESSMENT OF GROUND WATER QUALITY AND IT STREATMENT AT URULI DEVACHI - R.B HANEGAONKAR,; P.A.HANGARGEKAR, (International Journal of Innovations in Engineering Research and Technology, 2021)
The Daily waste generation in Punecity is 1000-1200mt/Dayof which 80% wastecollection anddisposal of waste at todumpsite every day. Thissolid waste is deposited at Urali Devachi Village. Thisopen dumping site has neither linear system nor other mechanism for groundwater pollution. Authorproposed to carry out the investigationintoground water qualityand aroundMunicipal Solid wastedumping site. Thestudy parameters for leach ateand groundwater quality were determined in the parameters likePh, Chloride,totalhardness.TDS,BOD,COD,Standardmethods were used for the analysis of the samples. Rag-pickers workers, vehicledrivers those residing nearer areasare continuously exposed and it becomes the source ofair pollution. Ithas been observed thatleachate originates from solid waste land. Thecommunity based on solid waste decomposition is a good andsafe disposal method, biologicaldecomposition of segregatedorganic waste is more useful forsolid waste management, and itcan easily convert waste to Fertilizer